Dendritic Zinc Growth on the Edges of Flat Steel Strip During Electro Galvanizing. (2015) - Bengoa, L.N.; Bruno, S.; Lazzarino, H.A.; Seré, P.R.; Egli, W.A.
Abstract: Dendritic growth on strip edges during continuous zinc electroplating of flat steel strip for the automotive industry is a well-known problem. They produce surface defects during the stamping process. In this work the effect of the electrolytic process variables on dendrites formation is studied. Zinc was electrodeposited on rotating steel discs. This new experimental configuration reproduces the hydrodynamic conditions and the current distribution found on the strip edge in an industrial zinc electroplating line. The tangential velocity of the outer edge of the discs was adjusted toa value equal to the relative speed between strip and fluid used in the industry. The effect of current density, temperature and edge roughness was evaluated. All these variables have a great influence on the size and morphology of dendrites.